The Estimation of relationship between actuarial rate of return, Maturity and Coupon: The case of Tunisia - ELMGUIRHI, SONIA (President University, 2024)
The aim of this paper is to study the estimation of the relationship between the actuarial rate of return, maturity, and coupon issued by the Tunisian banking and financial institutions, knowing that it is a significant component of financing. Therefore, this relationship issue is an essential link between investments. An important first step is to study yield bonds. For various forms of financial research.To date, the research has primarily focused on the yield bonds for institutions, except for studies conducted by institutions, financial and banking. There are regression models that are tested by different methods. The first model focuses only on the relationship between the actuarial rate of return, maturity, and coupon. The other models are prominently featured in the published literature regarding the yield of bonds. From these models, we discovered that the interest rate has an impact on the yield bonds. These results indicate that the maturity and coupon have a significant impact and exhibit a favorable correlation with the actuarial rate of return. Our estimation of our models proves to provide a high level of explained variation in the yields observed in the Tunisian bonds market